Evaluation of the Effect of Body Position on Intraocular Pressure Measured with Rebound Tonometer - Mayalı, Hüseyin (Turk J Ophthalmol, 2019)
OBJECTIVES: It is important to determine variables that influence intraocular pressure (IOP) measurement. This study aimed to evaluate the effect of body position on IOP. MATERIALS AND METHODS: The study included 52 right eyes of 52 patients who presented to the ophthalmology department of our hospital and had no ocular disease except refractive errors. IOP was measured with an Icare PRO tonometer while patients were in sitting, standing, and supine positions, with intervals of 10 minutes between the positions. Correlations between the results were evaluated using Spearman’s correlation analysis and Wilcoxon tests. RESULTS: Thirty-six of the 52 patients were female, 16 were male. Mean age was 31.65±6.30 (23-47) years. Mean IOP values in the sitting, standing, and lying positions were 17.76±3.41 (12.70-25.60) mmHg, 17.10±3.27 (11.50-25.20) mmHg, and 18.46±4.67 (10.50-29.40) mmHg, respectively. There were no statistically significant differences between measurements taken in the different positions (p=0.112, p=0.472, p=0.071). We observed that there was no relationship between age and body position (p>0.45, p>0.79, p>0.77) or between gender and position (p>0.59, p>0.69, p>0.54). CONCLUSION: Gender and age had no effect on IOP measured in different body positions. There were also no significant differences between IOP values measured in the different positions. Therefore, we believe the portable Icare PRO tonometer can be used for patients who are confined to bed and will provide IOP measurements that are concordant with values obtained while sitting.